PEOPLE MANAGEMENT AND STRATEGIC PLANNING IN HOSPITALS OF SOUTH OF MINAS GERAIS: AN ANALYSIS OF INDICATORS - Pinto, Lauisa Barbosa; Vilas Boas, Ana Alice; Antonialli, Luiz Marcelo; Silva, Nayara Rezende (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
Hospitals are highly specialized organizations inserted in a complex and hostile environment, being under the influence of political, economic and social variables. The present work brings up the discussion on the importance of using administrative tools, seeking answers to the following questions: How does strategic planning is perceived and performed by the managers of the public hospitals? How does Human Resources Management is perceived by the managers of these hospitals? What is the relationship between strategic planning and Human Resource Management? This article focuses on the implementation of a questionnaire published by Peabiru Institute, funded by the Avina Foundation in 2001, which includes seven indicators. The present study approaches two of these indicators (Human Resource Management and strategic planning) that can be used as an additional tool for organizations to assess their activities, identify priority issues and establish policies and guidelines that are able to optimize their results.